Why don’t students draw when learning from science texts? - Eidman, Leaha; Fiorella, Logan (Frontiers in Education, 2024)
This study explored why students rarely create drawings when learning from science texts despite potential learning benefits. Undergraduates (n = 114) studied a 10-part text on the human respiratory system and took notes by choosing their own strategies (free choice group) or by choosing to create a drawing or write a verbal summary (forced choice group). Other students were instructed to create drawings (draw group) or write summaries (summarize group). All students then completed a series of post-tests. The forced choice group chose to draw significantly more frequently than the free choice group; however, both groups still overwhelmingly chose summarizing. Participants across all groups reported lower prior experience, lower expectancies for success, lower perceived value, and higher perceived cost of drawing compared to summarizing. Students' prior experiences and beliefs about drawing were also associated with how frequently they chose to draw, providing implications for future instructional interventions.